Board characteristics, asset quality, and firm profitability: evidence from the ghanaian banking sector - GYIMAH MICHAEL BAAFI (KNUST, 2024)
A thesis submitted to the department of accounting and finance, Kwame Nkrumah university of science and technology, in partial fulfilment of the requirements for the award of master of business administration (finance)